Penerapan Model Discovery Learning Berbantuan Moodle untuk Meningkatkan Hasil Belajar Bahasa Inggris - Endang Sugiharyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims to improve student learning outcomes by utilizing Moodle to support learning using discovery learning models. This research is a Classroom Action Research (CAR) with the object of research being class XII TKR A students at SMK Negeri 1 Ponjong. In this research, it was conducted in 2 cycles starting from planning, implementing, observing, reflecting, and revising. The findings in the study show that applying the Moodle-assisted discovery learning model works better than using traditional learning methods. The results showed that the percentage of completeness of student learning outcomes increased, this can be seen through student learning outcomes during the English learning process. This occurs in each action cycle resulting in an increase in the completeness of student learning outcomes. It can be seen from the data on the initial scores of students that 54% of students got a complete score. In cycle I, it was recorded that 68% of students got a complete score and in cycle II, it was recorded that 85% of students got a complete score. So that this research was declared successful, there was an increase in the completeness of student learning outcomes, in cycle I there was an increase in the percentage of 14% from the initial data on student learning outcomes. In cycle II there is an increase in the percentage of 17% from cycle I data.